Kloning gen virulen Streptococcus agalactiae sebagai bahan dasar vaksin rekombinan - Sutanti, ,; Soejoedono, Retno Damayanti; Faizal, Irvan (Indonesian Society of Scientific Aquaculture (ISSA), 2016)
ABSTRACT Streptococcus agalactiae has emerged as an important pathogen that affects Nile tilapia in Indonesia aquaculture. Vaccination is one of the most effective tools for enhancing host defense and protecting fish from pathogens. DNA vaccine is a third generation of vaccines based on the gene encoding a vaccine antigen rather than the antigen itself. Mga is DNA-binding protein that activates expression of several important virulence gene, including those encoding M protein (emm), C5a peptidase (SCPA) and mga. The goals of this study were to isolate and molecular characterize the mga gene of local isolate of S. agalactiae to support the development of DNA vaccine. Local bacterial strain was isolated from Nile tilapia farming in West Java, Indonesia. Bacterial identification was accomplished by PCR, using 16S rRNA primers, which revealed the 1,500 bp PCR product. Mga gene isolation was accomplished by PCR using mga gene S. agalactiae SAF and SAR- specific primers, which revealed the 1,494 bp PCR product. Mga gene was cloned into pGEM T-easy and sequenced using M13 primers. SalI and NotI restriction enzymes were used to digest the pGEM T-easy vector containing mga gene. Mga gene was cloned into pMBA containing beta actin promoter of Japanese medaka. The 16S rRNA sequence analyses confirmed that the local bacteria was 97% similarity with S. agalactiae strain 15-92MPnew. The nucleotide sequence analyses confirmed that the clones were contained 98% similarity with M protein mga S. agalactiae. The mga gene controlled by MBA promoter has constructed successfully as a candidate of DNA vaccine to against S. agalactiae infection in Nile tilapia. Keywords: DNA Vaccine, Streptococcus agalactiae, mga gene, Oreochromis niloticus, recombinant DNA ABSTRAK Streptococcus agalactiae merupakan patogen penting yang mempengaruhi budidaya ikan nila di Indonesia. Vaksinasi merupakan salah satu metode yang paling efektif untuk meningkatkan pertahanan dan melindungi ikan dari patogen. Vaksin DNA adalah vaksin generasi ketiga yang mengandung gen penyandi antigen vaksin. Mga adalah protein DNA-binding yang mengaktifkan ekspresi beberapa gen virulensi, termasuk M protein (emm), C5a peptidase (SCPA) dan mga. Tujuan dari penelitian ini adalah untuk mengisolasi dan karakterisasi secara molekuler gen mga dari isolat lokal S. agalactiae untuk mendukung pengembangan vaksin DNA. Identifikasi bakteri dilakukan dengan PCR, menggunakan primer 16S rRNA dengan produk PCR 1.500 bp. Isolasi gen mga dilakukan dengan metode PCR menggunakan primer SAF dan SAR dengan ukuran target 1.494 bp. Gen mga dikloning ke vektor pGEMT–easy dan disekuensing menggunakan primer M13. Enzim Sal I dan Not I digunakan untuk memotong gen mga dari vektor pGEMT- easy, selanjutnya gen mga dikloning ke vektor pMBA yang mengandung promoter beta-aktin ikan medaka Jepang. Berdasarkan analisis menggunakan gen 16S rRNA diperoleh bahwa sampel memiliki kesamaan 97% sebagai S. agalactiae. Analisis sekuen nukleotida menunjukkan bahwa klon mengandung gen mga dengan 98% kesamaan dengan M protein mga S. agalactiae. Konstruksi mga gene yang dikendalikan oleh promoter MBA telah berhasil dibuat dan ini merupakan kandidat vaksin DNA untuk mengendalikan infeksi S. agalactiae pada ikan nila. Kata kunci: Vaksin DNA, Streptococcus agalactiae, gen mga, Oreochromis niloticus, DNA rekombinan